Effect of artificial food colours on childhood behaviour. Issue 1 (January 1990) - Pollock, I; Warner, J O
Abstract : We performed an objective evaluation of 39 children whose behaviour was observed by their parents to improve on an artificial food additive free diet and to deteriorate with dietary lapses. Only 19 children completed a double blind placebo controlled challenge study with artificial food colours. In these children food colours were shown to have an adverse effect on a daily Conners' rating of behaviour, but most parents could not detect these changes. A pharmacological mechanism of food additive intolerance is proposed to explain these effects.